Perceived key elements of a successful residential food waste sorting program in urban apartments: stakeholder views. (15th October 2016) - Xu, D.Y.; Lin, Z.Y.; Gordon, M.P.R.; Robinson, N.K.L.; Harder, M.K.
Abstract: A large, successful, residential food waste sorting (recycling) program in urban high-density housing was studied to elicit perceptions of the key elements of its success. An embedded mixed-methods approach was used with rigorous quantitative measures of weights and compositions of the waste to confirm the success of the program, combined with in-depth semi-structured interviews of stakeholders to reveal their opinions of the elements key for success. The program produced a 70% food waste capture rate slowly decreasing to 45% over 54 weeks, with <1% contamination. The key elements for success were found to relate to clarification of roles and responsibilities, and the usefulness of a 'broker' (here, an NGO (non-governmental organisation)) to co-develop new boundaries for stakeholder responsibilities. Residents first needed to be convinced of the serious intention of the local government to implement the policy, but then viewed waste sorting as a civic duty. This is different to the moderator of "authority' in earlier studies. The use of volunteers to demonstrate and interact on a personal level with residents was seen as a key element. The three month period of volunteer involvement was seen as key to good habit forming. Highlights: A large urban program captured 70% of residential food waste from apartments. In-depth stakeholder interviews elicited exploratory perceived key elements. Clarification and evolution of roles and responsibilities was key: an NGO helped. A visibly serious intention of policy elicited civic duty responses from residents. Volunteers manning waste stations 4 h/day for 3 months produced a key motivation effect.